Proportion of Sawdust as Carbon Sources in Rabbit Manure Compost for Increasing the Growth of Pennisetum purpureum cv Mott - Rahmi Dianita; Wiranto Wiranto; Muhammad Koyum; Ubaidillah Ubaidillah; Dodi Devitriano (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The right proportion of carbon in high N organic matter source in composting process will result good decomposition process. In this study, rabbit manure was composted with different portion of sawdust, and then the chemical properties were evaluated. The compost then applied to determine the growth response of dwarf elephant grass (Pennisetum purpureum cv. Mott) in terms of plant height, number of leaves, root and shoot dry matter, shoot and shoot ratio, and N content in shoot. The results showed that compost consisted of rabbit manure + sawdust with the ratio of 3:1 and 1:1 had good chemical properties (pH around 7.56 - 7.94, C/N ratio 17 – 19, C- organic 19 – 24%, Nitrogen 0.84 – 1.31%, Phosphor 0.43 – 0.82%, and Potassium 0.27– 0.37%) as well as sole rabbit manure compost. Applying compost to Mott grass resulted a good growth response which reflected in plant height (78.29 - 83.46 cm/plant), leaves number (53.50 - 57.92 blades), shoot dry matter (39.69 – 54.56 g DM/plant), root dry matter (16.50 – 18.16 g DM/plant), shoot : root ratios (2.52 - 3.20), and shoot N content (37.14 - 48.55 g DM/plant). The study concluded that compost rabbit manure + sawdust with ratio of 3:1 resulted the same growth response with sole rabbit manure compost.